Revisão sistemática sobre produção de vídeos na escola para alunos surdos - Kawase, Eduarda Megumi (Universidade Federal de São Carlos, 2020)
With more signs inscribed in the visuality and the disposition of the deaf, the learning process can be more accessible. Thus, in addition to privileging sign language, there is a need to privilege the use of instruments that are constituted in and by visuality, thus emphasizing video as an important medium to be used in the education of the deaf. In this research we asked about the existence of video productions in the school context of deaf students, so this research aimed to investigate dissertations and theses that presented the theme “video production in school for deaf students”, in electronic databases, in the period from 2005 to 2019. From the specific objectives, we sought to characterize the circumscribed dissertations on the theme “video production at school for deaf students” and describe and analyze how these video productions presented in the dissertations deal with deaf students' learning and concept formation based on the historical-cultural theoretical and visuality. The results showed that video production at school for deaf students has been taking place in some realities. From the video productions presented in the works, we note on the one hand the use of video as an instrument that accompanies the activities of deaf students and on the other as a medium that provides learning. With the study we have evidenced that the video productions present contributions to the education of the deaf and that in relation to the aid in the formation of scientific concepts, this develops when students are involved in the video production process, in this type of proposal students actively participate of activity, which favors interaction with peers and with the subject studied, as well as narrating and recording in the first language, which enables the organization of thought through sign language.
Systematic review on video production in school for deaf students
Keywords: Educação Especial; Educação bilíngue para surdos; Visualidade; Vídeo; Revisão sistemática; Special Education; Bilingual education for deaf; Visuality; Video; Systematic review; CIENCIAS HUMANAS::EDUCACAO